Інновації і технологічні уклади в парадигмі розвитку економіки та інформаційного суспільства - Дуброва, Наталя Петрівна; Dubrova, Natalia.; Крючко, Леся Станіславівна; Kriuchko, Lesia (Чорноморський національний університет імені Петра Могили, ТОВ `ДКС Центр`, 2023)
Стаття присвячена дослідженню взаємозв'язку між розвитком суспільства та економіки, інформаційних революцій та технологічних укладів. В роботі використаний аналіз наукових досліджень в сфері інноваційного розвитку, інформаційних революцій та технологічних укладів та їх вплив на розвиток економіки та суспільства. Розглянуті сім інформаційних революцій та технологічних укладів, що виникали на певних періодах розвитку людства. Проведений аналіз дав можливість розглянути синхронність інформаційних революцій та формування технологічних укладів і їх вплив на розвиток суспільства. В дослідженні зазначено, що основою та розвитком технологічних укладів є інформаційні революції, когнітивна здатність людини опрацьовувати інформацію та використовувати її для створення суспільних благ. Визначено, що розвиток суспільства та його добробут напряму залежить від розвитку інтелектуального та наукового потенціалу, розвитку технологічних укладів та впровадженні інновацій, що формують цивілізаційний рівень. В роботі акцентується увага на освіті та науці, що сприяє формуванню інтелектуальної еліти, яка здатна до сприйняття інноваційних ідей і від якої залежить розвиток економіки, суспільства і нації в цілому. The article is devoted to the study of the relationship between the development of society and the economy, information revolutions and technological systems. The paper is used the analysis of scientific research in the field of innovative development, information revolutions and technological systems and their influence on the development of the economy and society. Seven information revolutions and technological structures that arose at certain periods of human development are considered. The conducted analysis made it possible to consider the synchronicity of information revolutions and the formation of technological structures and their effect on the development of society. The article states that the basis and development of technological systems are information revolutions, human cognitive ability to process information and use it for creation of public goods.It was determined that the development of society and its well-being directly depends on the development of intellectual and scientific potential, the formation of technological structures and the introduction of innovations that form the level of civilization. The work focuses on education and science, which contributes to the formation of intellectual elites that is capable of perceiving innovative ideas and depends on the development of the economy, society and the nation as a whole. The scientific, technical and informational revolutions, the emergence and development of technological systems related to innovative development. It is at this moment that man and his scientific and educational potential act as the driving factor of socio-economic progress. In a society where human creativity, generation of ideas, innovations and innovations are valued, conditions are created for revealing potential of both: a person and a country. A society focused on innovation is a source of competitive advantages, the basis of which is new knowledge, ideas and information. Orientation to an innovative model of economic development should ensure an increase in funding for education, fundamental and applied science, measures for popularization (marketing) and implementation of scientific developments. The latter statement should be implemented by the state innovation policy at the expense of the state budget. Another component of the innovative model is education and educational activity, which is the basis of human capital development. As the scientists note, it is the rise in the level of education that will allow creating an environment that will perceive and generate new ideas, adapt them and create new knowledge, which is the basis for innovative development. That is why one of the most important tasks is to create such conditions that will contribute to the development of the creative potential of each person and their motivation to participate in innovative activities
Innovations and Technological Structures in Paradigm of Development of the Economy and the Information Society
Keywords: інновації; Innovations; інноваційний розвиток; innovative development; інформаційна революція; nformation revolution; технологічні уклади; technological systems; науково-освітній потенціал; scientific andeducational potential